Economic, political and social impact on the fuel and (LPG) subsidy in Ecuador - Beltrán Ruiz, José Andrés; Velasteguí Rubio, Sharon Luathani (SATHIRI, 2021)
This research document includes some criteria on the importance of fuel and LPG subsidies on the Ecuadorian economy, that is why, an account is made of the historical evolution during the last 40 years in which Ecuador lives in democracy, after having gone through a dictatorial process, whose main primary product in the structure of its general state budget is oil. For the elaboration of this work, the bibliographic review method is used, that is, it is based on some research sources, in order to determine the economic, political and social impact generated by the subsidy to oil derivatives, especially what has to do with fuels and LPG. Well-applied subsidies allow the redistribution of wealth, they become incentives for industries, but subsidies for fuels and LPG over time have generated a distortion in the economy, making it even an economic and political problem. The public debate is whether they should be maintained or eliminated entirely, despite the fact that fuel subsidies have their price band.